A review of the impact of noise restrictions at airports. (January 2017) - Rodríguez-Díaz, A.; Adenso-Díaz, B.; González-Torre, P.L.
Highlights: One big obstacles of air traffic management expansion is environmental concerns. A regulation and operation procedures implemented summary is provided. It is necessary to improve modelling-simulation-monitoring noise evaluation tools. Optimization tools that take into account the noise problem are analysed. Abstract: One of the biggest obstacles to the building of new airports and expanding runway capacity is environmental concerns, especially noise. In this paper, we review what has been previously studied in the literature concerning the noise reduction problem around airports from the Air Traffic Control (ATC) perspective. In order to facilitate the knowledge of the current situation, a regulation summary from the USA and EU is provided. We mainly focus our research on operational procedures, since they are one of the easiest improvements nowadays for reducing the impact of noise around airports. Moreover, the paper sums up the modelling, monitoring and simulation tools related to noise at airports proposed in the literature. Finally, special care is taken to review the optimization tools, the objective of which is to take into account the noise problem in order to help, or propose alternatives, to reduce its impact from airport operations.